GAMBARAN KUALITAS HIDUP PASIEN KANKER LIMFOMA NON HODGKIN YANG DIRAWAT DI RSUP SANGLAH DENPASAR (STUDI PENDAHULUAN) - Sutrisno, Heri; Dharmayuda, Tjokorda Gde; Rena, Renny A (journal of internal medicine, 2012)
Quality of life was a target therapy in cancer patients especially on metastatic cancer. Quality of life currently have becomeone of stadard for therapeutic evaluation. Because quality of life was a subjectif characteristic and can only measure by patient, so measuring quality of life patients must use multidimensional measure tool that offend aspect from physical, social and emotional, simple, easy to understand and answer by all patients and must to validated. To observe description of quality of life from cancer patient of Non Hodgkin Lymphoma (NHL) which admitted in Sanglah Hospital Denpasar, we have done analytic descriptive research on NHL patients with used EORTC QLQ-C30 questioner. Fifteen of NHL patients which cared in Internal Department Sanglah Hospital on January ? June 2010, 12 (80%) were male and 3 (20%) were female. Good quality of life was 8 (53.3%), moderate was 5 (33.3%) and poor was 2 (13.2%). From 10 (66.7%) patients undergone chemotherapy, good quality of life was 5 (50%), moderate was 3 (30%) and poor was 2 (20%). There is correlation between quality of life of NHL patients with grading of clinical disease (p = 0.032; r = -0.554), there is no correlation quality of life with giving chemotherapy in NHL patients (p = 0.560; r = -0.164). Meassuring quality of life NHL patient with EORTC QLQ-C30 was correlated with Karnofsky score (p = 0.031; r = 0.557) and ECOG (p = 0.04; r = -0.699).
Keywords: quality of life, NHL, Sanglah Hospital